Nutritional Analysis and Acceptability of Cookies Made from Pontianak Taro Flour (Colocasia esculenta L. Schott) with the Addition of Kepok Banana Flour (Musa paradisiaca forma typica) as a Snack for School Children - Jihan Rizla Megadianti; Jonni Syah R. Purba; Shelly Festilia Agusanty (MEDICA (International Medical Scientific Journal), 2023)
School-aged children are generally in a period of rapid growth and high activity, making nutrition a crucial factor in their physical development and cognitive intelligence. Inadequate nutrition can hinder physical growth, mental development, and thinking ability. Nutritional intake can be obtained from daily food consumption, including snacks. Snacks are widely favored across all age groups, from children to adults, and are typically provided in small portions, contributing around 10%–20% of daily energy needs. One popular and easy-to-make snack for children is cookies. This study aims to analyze the nutritional content and acceptability of cookies made from Pontianak taro flour (Colocasia esculenta L. Schott) with the addition of Kepok banana flour (Musa paradisiaca forma typica) as a snack for school children. The research method used is experimental. The treatments applied were variations in taro and banana flour proportions: F1 (75% : 25%), F2 (50% : 50%), and F3 (25% : 75%). The tests conducted included organoleptic tests to assess consumer preference and chemical analysis to determine nutrient content. The organoleptic test results—covering color, aroma, taste, and texture—showed that the F3 formulation (25% Kepok banana flour and 75% Pontianak taro flour) received the highest total score of 236. The chemical analysis per 100 grams of the F3 formulation showed protein content of 5.535%, fat 28.214%, carbohydrates 10.635%, ash content 1.451%, and moisture content 4.470%. In conclusion, among the three formulations, F3 was the most preferred in terms of acceptability, with favorable nutrient content suitable for a school children's snack.